Strain Sensors: Coco Stretch: Strain Sensors Based on Natural Coconut Oil and Carbon Black Filled Elastomers (Adv. Mater. Technol. 2/2021). Issue 2 (8th February 2021) - Lugoda, Pasindu; Costa, Júlio C.; Garcia‐Garcia, Leonardo A.; Pouryazdan, Arash; Jocys, Zygimantas; Spina, Filippo; Salvage, Jonathan; Roggen, Daniel; Münzenrieder, Niko
Abstract : An inexpensive biocompatible strain sensor constituting of an elastomer filled with natural coconut oil and carbon black is shown by Pasindu Lugoda and co‐workers in article number 2000780 . The easily manufacturable and eco‐friendly fabrication technique enables the creation of strain sensors in environments where standard electronic/chemical fabrication facilities are unavailable, like in schools and developing countries. These devices stretch to 1035% and are utilized for smart textile applications.